Desenvolvimento de um método molecular para identificação de híbridos de euinos (Equus caballus) e jumentos (Equus asinus) e caracterização do perfil bioquímico sérico de bardotos e de jumentos da raça Pêga - Santos, João Batista Ferreira dos (2016)
The horses have great economic importance, being widely used in farms, leisure and sport. Hybrids (mules and hinnies) are poorly studied animals and can be confused due to the great phenotypic similarity between them. Additionally, analysis of serum biochemical profile of hybrids and donkeys is generally performed using the standard equine erroneously. In this context, the objectives of this study were: 1) to develop a rapid and accurate test based on the evaluation of mitochondrial DNA hinnies and mules, to differentiate them through a PCR-Multiplex; 2) characterize the serum biochemical profile hinnies and donkeys the Pega breed and investigate whether there is influence of age and sex on serum biochemical components of these animals. For the development of molecular test to identify mules and hinnies three primers specific for the D-loop mtDNA region were designed and a multiplex PCR was developed and validated using DNA samples from 77 animals (horses, donkeys, mules and hinnies) from different sources. Mitochondrial DNA asses rise generates a specific amplicon of 689 base pairs and a source of equine 620 base pairs. Thus, the test allows to accurately identify maternal origin of the hybrid, which is sufficient to determine whether the animal is a mule or hinny. For the evaluation of serum biochemical parameters of hinnies blood samples from 15 animals were used, eight males aged between 14 and 84 months and seven females aged 6 to 84 months. It was found that the albumin globulin ratio A:G, calcium and Ca: P ratio higher values for animals aged less than 30 months. The results showed that with respect to the serum biochemical profile hinnies was differences in age, but not to sex. To asses were analyzed blood samples from animals of the handle class 123, of which 29 were males aged between 8 days and 10 years and 94 females between 2 days and 12 years of age. Among the age groups, there was statistical difference in the total protein, albumin, cholesterol, triglycerides, creatinine, phosphorus, calcium, Ca:P ratio, magnesium, AST, alkaline phosphatase and GGT. Sex influenced the values of total protein, globulin, triglycerides, ratio A:G, phosphorus, calcium and CK. Note that if the serum biochemical parameters of donkeys Pega breed were influenced by age and sex. In conclusion, the results obtained in this work can be used by farmers, breeders and veterinarians, are important for research, clinical and agribusiness equines.